2018
DOI: 10.1152/ajpendo.00426.2017
|View full text |Cite
|
Sign up to set email alerts
|

Reduced skeletal muscle phosphocreatine concentration in type 2 diabetic patients: a quantitative image-based phosphorus-31 MR spectroscopy study

Abstract: Mitochondrial function has been examined in insulin-resistant (IR) states including type 2 diabetes mellitus (T2DM). Previous studies using phosphorus-31 magnetic resonance spectroscopy (P-MRS) in T2DM reported results as relative concentrations of metabolite ratios, which could obscure differences in phosphocreatine ([PCr]) and adenosine triphosphate concentrations ([ATP]) between T2DM and normal glucose tolerance (NGT) individuals. We used an image-guided P-MRS method to quantitate [PCr], inorganic phosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 63 publications
(99 reference statements)
1
14
1
1
Order By: Relevance
“…These participants, while all obese, had a wide range in muscle mass markers (skeletal muscle index [SMI]: 6.2–11.0 ALM/hr 2 ; muscle volume: 1,073.1–2,709.4 cm 3 ) as well as muscle functionality (peak power: 25.0–227.8 W). Despite other reports linking phosphorus metabolites with insulin sensitivity (Ripley et al, 2018; Szendroedi et al, 2011), we found that type 2 diabetes status did not influence the in vivo metabolic phenotype (data not shown), and therefore, all subjects were grouped for correlative analyses. Next, we examined relationships with body composition measurements and found that SMI, an index of muscle mass used to define sarcopenic status, was associated with two metabolites, PCr ( r = .365; p ‐value = .008) and PDE2 ( r = −0.366; p ‐value = .008).…”
Section: Resultscontrasting
confidence: 90%
See 3 more Smart Citations
“…These participants, while all obese, had a wide range in muscle mass markers (skeletal muscle index [SMI]: 6.2–11.0 ALM/hr 2 ; muscle volume: 1,073.1–2,709.4 cm 3 ) as well as muscle functionality (peak power: 25.0–227.8 W). Despite other reports linking phosphorus metabolites with insulin sensitivity (Ripley et al, 2018; Szendroedi et al, 2011), we found that type 2 diabetes status did not influence the in vivo metabolic phenotype (data not shown), and therefore, all subjects were grouped for correlative analyses. Next, we examined relationships with body composition measurements and found that SMI, an index of muscle mass used to define sarcopenic status, was associated with two metabolites, PCr ( r = .365; p ‐value = .008) and PDE2 ( r = −0.366; p ‐value = .008).…”
Section: Resultscontrasting
confidence: 90%
“…Though not as well studied, recent evidence has revealed that resting in vivo phosphorus metabolite levels may relate to whole‐body and muscle‐specific phenotypes. Previous reports have shown dysregulation of resting in vivo phosphorus metabolites under pathological conditions, including obesity, type 2 diabetes, spinal cord injury, and muscular dystrophy, and appear to be linked to clinical measures of glycemic control and body composition (Hooijmans et al, 2017; McCully, Mulcahy, Ryan, & Zhao, 2011; Ripley et al, 2018; Szendroedi et al, 2011). Specifically, resting phosphocreatine (PCr) levels have been shown to be negatively associated with HbA1c and fasting glucose levels, while heightened levels are linked with elevated intracellular ATP levels (Ripley et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In human patients with type II diabetes, ATP and ADP were measured in vivo in vastus lateralis [67]. Compared to age, sex, and BMI matched non-diabetic controls, diabetic patients display significantly less ATP, ADP, and PCr (phosphocreatine).…”
Section: Diabetesmentioning
confidence: 99%